Endocytosis and Intracellular Trafficking Properties of Transferrin-Conjugated Block Copolypeptide Vesicles - Choe, Uh-Joo (2013)
Block polypeptides are an emerging class of materials that have the potential to be used in many biomedical applications, including the field of drug delivery. We have previously developed a negatively charged block copolypeptide, poly(L-glutamate)(60)-b-poly(L-leucine)(20) (E(60)L(20)), which forms spherical vesicles in aqueous solution. Since these vesicles are negatively charged, they are minimally toxic toward cells. However, the negative charge also inhibits these vesicles from effectively being internalized by cells, which can be problematic as many therapeutics have intracellular targets. To overcome this limitation of the E(60)L(20) vesicles, transferrin (Tf) was conjugated onto the vesicle surface, since the receptor for Tf is overexpressed on cancer cells. The enhanced uptake of the Tf-conjugated vesicle was verified through confocal microscopy. Furthermore, endocytosis and immunostaining experiments confirmed that the Tf conjugated on the vesicle surface plays a critical role in the internalization and subsequent intracellular trafficking behavior of the vesicles.